Analisis kemampuan scientific literacy siswa SMA dalam soal PISA pada materi virus dan bakteri - Fadillah, Nuke Siti; Rustaman, Nuryani; Kusumawaty, Diah (Assimilation: Indonesian Journal of Biology Education, 2021)
This study aims to analyze the scientific literacy skills of high school students on PISA released items reading and science questions based on the PISA framework on the "Process Aspects" in terms of scientific literacy and reading literacy on the biological content of the material "Viruses and Bacteria". This research is a descriptive study with a quantitative approach. The instruments used were PISA questions in 2000, 2006, and 2015 which have been released (main instrument) as well as school curriculum biology questions (comparative instruments), questionnaires, and interviews. The research began to be carried out in February 2020 and began with conducting research trials conducted in schools (A). The subjects in this study were students in SMA (B) and (C) grades 10, 11, and 12 with different school curriculum characteristics, school (B) with the 2013 curriculum and school (C) with the Cambridge curriculum. Sampling was carried out using convenience sampling method. The results showed that the scientific literacy skills of school B students resulted in: 80% (grade 10), 81% (grade 11) and 75% (grade 12) in the "High" category, school C resulted in: 47% (grade 10), 51% (grade 11) and 55% (grade 12) in the "Very Low" category. The students' results in the 2013 school curriculum biology questions (B) were included in the "Very High" category, while schools (C) that used the Cambridge curriculum were included in the "Low" category. Acquisition of scientific literacy skills which is included in the "High" category is in line with the experience of students in learning in schools which as a whole uses the PBL (Problem Based Learning) method, while the acquisition of scientific literacy skills which is included in the "Low" category turns out to be less in line with students' experiences in learning. in schools that as a whole use the PjBL (Project Based Learning) method.